ChemInform Abstract: Mild Copper—TBAF‐Catalyzed N‐Arylation of Sulfoximines with Aryl Siloxanes. Issue 10 (March 2015) - Kim, Jaeeun; Ok, Jinpyo; Kim, Sanghyuck; Choi, Wonseok; Lee, Phil Ho
Abstract The coupling of sulfoximes with arylsiloxanes in the presence of oxygen using a catalytic combination of CuI and Bu4F under mild reaction conditions is developed.